One-mSv CT colonography: Effect of different iterative reconstruction algorithms on radiologists’ performance - Shin, Cheong-Il; Kim, Se Hyung; Im, Jong Pil; Kim, Sang Gyun; Yu, Mi Hye; Lee, Eun Sun; Han, Joon Koo (European journal of radiology, 2016)
•Mean effective radiation dose for 120kVp/100kVp with 10mAs CT colonography was 1mSv.•Image noise significantly decreased from FBP to ASIR and MBIR algorithms.•Per-polyp sensitivity of 1mSv CT colonography reconstructed with FBP was not acceptable.•Per-polyp sensitivity of 1mSv CT colonography can be improved with iterative reconstruction algorithms.•1mSv CT colonography with MBIR reconstruction can be useful with acceptable diagnostic performance for clinically significant polyps. To analyze the effect of different reconstruction algorithms on image noise and radiologists’ performance at ultra-low dose CT colonography (CTC) in human subjects. This retrospective study had institutional review board approval, with waiver of the need to obtain informed consent. CTC and subsequent colonoscopy were performed at the same day in 28 patients. CTC was scanned at the supine/prone positions using 120/100kVp and fixed 10mAs, and reconstructed using filtered back projection (FBP), adaptive statistical iterative reconstruction (ASIR), and model-based IR (Veo) algorithms. Size-specific dose estimates (SSDE) and effective radiation doses were recorded. Image noise was compared among the three datasets using repeated measures analysis of variance (ANOVA). Per-polyp sensitivity and figure-of-merits were compared among the datasets using the McNemar test and jackknife alternative free-response receiver operating characteristic (JAFROC) analysis, respectively, by one novice and one expert reviewer in CTC. Mean SSDE and effective radiation dose of CTC were 1.732mGy and 1.002mSv, respectively. Mean image noise at supine/prone position datasets was significantly lowest with Veo (17.2/13.3), followed by ASIR (52.4/38.9) and FBP (69.9/50.8) (P<0.0001). Forty-two polyps in 25 patients were reference polyps. For both readers, per-polyp sensitivity of all 42 polyps was highest with Veo reconstruction (81.0%, 64.3%), followed by ASIR (73.8%, 54.8%) and FBP (57.1%, 50.0%) with statistical significance between Veo and FBP for reader 1 (P=0.002). JAFROC analysis revealed that the figure-of-merit for the detection of polyps was highest with Veo (0.917, 0.786), followed by ASIR (0.881, 0.750) and FBP (0.750, 0.746) with statistical significances between Veo or ASIR and FBP for reader 1 (P<0.05). One-mSv CTC was not feasible using the standard FBP algorithm. However, diagnostic performance expressed as per-polyp sensitivity and figures-of-merit can be improved with the application of IR algorithms, particularly Veo.